Hubungan Usia Terdiagnosis dengan Status Gizi dan Pubertas Pasien Thalasemia Beta Mayor di Poli Anak RSUD Al Ihsan - Annisa Berlia Maharani Kaka Nisa; Agung Firmansyah Sumantri; Yuliana Ratna Wati (UNISBA Press, 2023)
Abstract. Thalassemia is a hereditary blood disorder that is commonly found in the world. It is estimated that thalassemia sufferers in West Java reach 40% of the total thalassemia patients in Indonesia. Most patients diagnosed with thalassemia are estimated at the age of 1-5 years. Growth and development disorders occur in patients with beta thalassemia major. Early diagnosis makes it possible to provide maximum management so as to minimize puberty delays and impaired nutritional status. This study aims to determine the relationship between diagnosed age and nutritional status and puberty in pediatric thalassemia patients at Al Ihsan General Hospital. The sample in this study were beta thalassemia major patients aged 13-18 years as many as 21 patients. This study used an observational analytic method with a cross-sectional study design. Data collection was carried out by direct examination and analyzed by fisher's exact test with SPSS software. The results showed that the diagnosed age was < 5 years 81% and > 5 years 19%, 23.8% poor nutritional status and 76.2% good nutrition, 19% late puberty and 81% not late. Bivariate results showed a relationship between age diagnosed and nutritional status (p=0.532) and puberty (p=0.546) in pediatric beta thalassemia patients at Al Ihsan Hospital. With adequate iron chelation therapy, it is hoped that thalassemic sufferers will experience the same growth and development as normal children. In this study, nutritional status and puberty did not show a relationship with the age at diagnosis because they were under control. Keywords: Age Diagnosed, Nutritional Status, Puberty, Thalassemia. Abstrak. Thalasemia merupakan kelainan darah herediter yang banyak ditemukan di dunia. Diperkirakan penderita thalasemia di Jawa Barat mencapai 40% dari total pasien thalasemia di Indonesia. Pasien yang terdiagnosis thalasemia terbanyak diperkirakan pada usia 1-5 tahun. Gangguan tumbuh kembang banyak terjadi pada pasien dengan thalasemia beta mayor. Diagnosis dini dimungkinkan pemberian tatalaksana yang maksimal sehingga meminimalisir keterlambatan pubertas dan gangguan status gizi. Penelitian ini bertujuan untuk mengetahui hubungan usia terdiagnosis dengan status gizi dan pubertas pada pasien thalasemia anak di RSUD Al Ihsan. Sampel pada penelitian ini adalah pasien thalasemia beta mayorberusia 13-18 tahun sebanyak 21 pasien. Penelitian ini menggunakan metode analitik observasional dengan desain penelitian cross-sectional. Pengumpulan data dilakukan dengan pemeriksaan secara langsung dan dianalisis dengan uji fisher exact dengan Software SPSS. Hasil penelitian menunjukkan usia terdiagnosis usia < 5 tahun 81% dan > 5 tahun 19%, status gizi kurang 23,8% dan gizi baik 76,2%, pubertas terlambat 19% dan tidak terlambat 81%. Hasil bivariat menunjukkan hubungan antara usia terdiagnosis dengan status gizi (p=0,532) dan pubertas (p=0,546) pada pasien thalasemia beta mayor anak di RSUD Al Ihsan. Dengan terapi kelasi besi adekuat diharapkan penderita thalasemia mengalami tumbuh kembang yang sama dengan anak normal. Pada penelitian ini status gizi dan pubertas tidak menunjukkan hubungan dengan usia terdiagnosis karena sudah terkendali. Kata Kunci: Status Gizi, Thalasemia, Usia Terdiagnosis, Pubertas.